Modeling of electrical characteristics of photo voltaic and effecting of cell parameters on V-I curve - S. Abdullah, Fawaz; A. Hamoodi, Safwan; N. Hamoodi, Ali (International Journal of Engineering and Technology, 2018)
Studding of PV systems in an active way needs accurate information of the power and voltage P-V current and voltage I-V characteristic curves of solar PV order. Therefore, this paper shows emulation of solar PV model utilizes Matlab/Simulink and practical results. This PV model depends on mathâ€™s equation and is explained during an equivalent circuit involving a photo current source, diode, shunt resistor and series resistor representing leakage current and series resistor expressing the inside losses because of the current flow. The advanced model let the prognosis of PV array manner under various circuit model and ecological parameters solar temperature, ray. A special model (Lcs M200 â€“ JA/SI) solar collector using for this paper, results was compared with practical curve with different points of the curve and show good conformity to the model. Â